An examination of the chance elements in Witold Lutosławski's music, with particular attention to its function as a model for compositional practice : a thesis and portfolio presented in fulfillment of the requirements for the degree of M.Mus. in Composition at the New Zealand School of Music, Wellington, New Zealand - Hextall, Pieta (Massey University, 2012)
This thesis studies the use of aleatory techniques in Witold Lutoslawski’s music and the issues that arise when using aleatoricism, a branch of textural composition that has room for exploration. I focused my study on three of Lutoslawski’s major works, analysing his approach to aleatoricism, form, and macro- and micro-rhythm. I wrote three works for the portfolio component. My approach to aleatoricism differed in each work. Through studying Lutoslawski and my own composition, I came across practical issues in creating the score, issues with performers, and compositional problems. However, once these issues were worked though, aleatoricism is a exciting compositional device that is not yet tired.
Keywords: Witold Lutosławski; Criticism and interpretation; Aleatory music; History and criticism; Composition (Music)